Early Discharge After Colorectal Resection: The Positive Impact of an Enhanced Recovery Program on a Rural Colorectal Surgery Service. Issue 6 (December 2016) - Tebala, Giovanni D.; Keane, Sean; Osman, Abdelsalam; Ip, Mina; Khan, Abdul Q.; Perrone, Luciano
Abstract : Background: Enhanced recovery (ER) programs are policies and protocols meant to improve postoperative recovery after surgery. As a consequence of a smoother recovery, patients can be discharged early. This paper describes the impact of an ER program in colorectal surgery in a rural hospital. Materials and Methods: In total, 132 patients had colorectal resection within the ER program. Data were collected prospectively. The ER pathway affects perioperative management in the following ways in order to: (1) improve patient's general condition before surgery, (2) minimize intraoperative surgical trauma by using a laparoscopic approach in all cases, and (3) facilitation of a quicker postoperative return of physiological function. Results: Most (86.4%) of the patients have been operated as elective cases and for a cancer (73.5%). Laparoscopic resection was performed in 63.6% of patients, with a conversion rate of 10.6%. Total morbidity was 18.2%, leak rate was 1.5%, and 90-day mortality rate was 3%. Overall median postoperative stay was 6.5 days. Total length of in-hospital stay was lower in laparoscopic resections (5.5 d), elective cases (6 d), and in younger patients (6 d). Age and laparoscopic access were independent prognostic factors significantly associated with early discharge in elective patients. Overall readmission rate was 9.1% and this was not affected by any preoperative or intraoperative factor within those in this study. Conclusions: The ER program positively impacted the outcome of colorectal resections also in our rural setting. Discharging patients expeditiously did not affect postoperative morbidity or readmission rate.